Adsorption of serum proteins on titania nanotubes and its role on regulating adhesion and migration of mesenchymal stem cells. Issue 11 (17th June 2020) - Wu, Sai; Zhang, Deteng; Bai, Jun; Zheng, Honghao; Deng, Jun; Gou, Zhongru; Gao, Changyou
Abstract: Migration and differentiation of bone marrow‐derived mesenchymal stem cells (BMSCs) is an important biological process in tissue regeneration. Nanostructured titanium materials are believed to play a fundamental role in dental and orthopedic applications. However, the protein adsorption on nanostructured titanium materials and its correlation with the subsequent cell behaviors have not been studied. In this work, the titania nanotube arrays with different tubular diameters ranging from 27.3 to 88.2 nm were fabricated by using an electrochemical etching method. The adsorbed amounts and types of cell adhesion‐related proteins (such as fibronectin, vitronectin, and laminin) from serum were investigated, revealing that these proteins were preferred to bind onto the surface with nanotubes of a smaller diameter. Adhesion and migration of BMSCs were studied as a function of different nanotube diameters in the presence or absence of serum proteins. Compared with the nanotube surface with a larger tubular diameter (88.2 nm), the surface with a smaller one could better support BMSCs in terms of adhesion and spreading. The pre‐adsorbed serum proteins significantly enhanced adhesion and migration abilities of BMSCs. However, the adequate interactions between cells and serum proteins on the nanotubes surface with smallest nanotubes in diameter weakened cell mobility. Arrangement of cytoskeleton and expressions of key genes and proteins were studied, revealing that the nanostructured surfaces and pre‐adsorbed proteins jointly mediated the adhesion and migration of BMSCs.